China’s Foreign Investment Law and TRIMs Agreement: Conflicts, Amendments, and Applications - Zhang, Xiao; He, Tong; Liu, Jiangwei (International Journal of Global Economics and Management, 2024)
This article explores the developmental trajectory of China’s Foreign Investment Law and its consistency issues with the WTO TRIMs Agreement. Covering four developmental stages from 1979 to 2020, it provides a detailed account of the evolution and amendments of China’s legal framework on foreign investment. The article identifies inconsistencies in national treatment, elimination of quantitative restrictions, and transparency principles, analyzing adjustments and revisions made across these stages to align with international trade environments and WTO requirements. Despite significant progress, the article highlights areas for further improvement, such as the implementation of national treatment principles and resolution of transparency issues.